Science and technology international integration by Vietnamese r&d organizations in Vietnam - current state and challenges - Bui Huy Hop,; Do Van Xuan, (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2022)
International cooperation and integration in science and technology were being organized and implemented as an integral part of science and technology (S&T) activities. They also are an important channel for mobilizing additional resources, knowledge, technology, and finance from outside to serve the development of Vietnam's science and technology. However, Vietnam's R&D organizations still face with many limitations in this activity due to the low human resources for research and limitation of investment for R&D’s activities, the timidity of using intermediary science and technology services especially the lack of reasonable mechanisms to encourage and promote the use of intermediary science and technology services. From the experience of many countries in the world, when focusing on building and developing integration of science and technology into essential public service activities, it has greatly contributed to promoting not only the development of science and technology but also economic and political stability in their own country and enhance their international reputation; In the context of the 4th industrial revolution and the current Covid-19 pandemic, the paper proposes a number of S&T integration solutions that should be prioritized for application to Vietnam's R&D organizations that includes improving the capacity of science and technology integration for R&D Orgnizations; raising awareness about S&T intermediaries; and apply the testing mechanism (Regulatory Sandbox) at R&D organizations in Vietnam. Code: 22033001